2021
DOI: 10.3892/etm.2021.10778
|View full text |Cite
|
Sign up to set email alerts
|

MEX3A knockdown inhibits the tumorigenesis of colorectal cancer via modulating CDK2 expression

Abstract: Colorectal cancer (CRC) is a malignant tumor of the gastrointestinal tract and a leading cause of cancer-associated mortality worldwide. Mex-3 RNA binding family member A (MEX3A) promotes the progression of multiple types of cancer, including ovarian and cervical cancer. However, to the best of our knowledge, the role of MEX3A in CRC is not completely understood. Therefore, the present study aimed to investigate the function of MEX3A in CRC. The mRNA and protein expression levels of MEX3A in CRC cells were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…In this study, we categorized HCC patients into three m7G clusters using consistent clustering and screened five prognostic m7G‐related genes, namely, MEX3A, G6PD, FAM83D, SPP1 and ADH. MEX3A functions as an oncogene in various cancers, including in breast and colorectal cancers 47,48 . In addition, Lu et al showed that MEX3A can promote angiogenesis in colorectal cancer through activating the glycolytic pathway, and concluded that MEX3A is a novel therapeutic target for cancer treatment 49 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we categorized HCC patients into three m7G clusters using consistent clustering and screened five prognostic m7G‐related genes, namely, MEX3A, G6PD, FAM83D, SPP1 and ADH. MEX3A functions as an oncogene in various cancers, including in breast and colorectal cancers 47,48 . In addition, Lu et al showed that MEX3A can promote angiogenesis in colorectal cancer through activating the glycolytic pathway, and concluded that MEX3A is a novel therapeutic target for cancer treatment 49 .…”
Section: Discussionmentioning
confidence: 99%
“…MEX3A functions as an oncogene in various cancers, including in breast and colorectal cancers. 47,48 In addition, Lu et al…”
Section: Specific Biological Functions Of Risk Scorementioning
confidence: 99%
“…Mex3 RNA-binding family member A (MEX3A) was originally identified as a translational regulator in Caenorhabditis elegans that binds RNA [ 5 , 6 ]. MEX3A has been previously reported to act as oncogene in a variety of cancers, such as breast cancer [ 6 ], CRC [ 7 ] and osteosarcoma [ 8 ]. For example, Liang et al [ 9 ] found that MEX3A promotes lung adenocarcinoma metastasis by down-regulating LAMA2 and then activating PI3K/AKT pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In the CRC study, Li et al [ 10 ] found that MEX3A benefits CRC tumorigenesis through RAP1/MAPK signaling. Zhou et al [ 7 ] revealed that MEX3A knockdown inhibits CRC tumorigenesis by up-regulating CDK2 expression. In conclusion, MEX3A is critical to CRC progression, but no studies have reported the role of MEX3A in CRC angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent reports have implicated MEX3A as an oncogene that promotes tumor growth and cancer cell invasion in a variety of cancers such as lung, breast and cervical cancer 20 - 22 . In addition, in vitro assays showed that MEX3A promotes the migration, invasion and proliferation of CRC cells 23 , 24 . However, it is still unknown of the function and molecular mechanism of MEX3A in coordinating self-renewal and differentiation signals in CRC.…”
Section: Introductionmentioning
confidence: 99%